Pengaruh Pembiayaan Mudharabah, Musyarakah Dan Ijarah Terhadap Profitabilitas Bank Umum Syariah Di Indonesia - Devi Sri Hartati; Dailibas Dailibas; Isro’iyatul Mubarokah (ITB AAS INDONESIA Surakarta, 2021)
Abstract This study aims to determine the effect of mudharabah, musyarakan and ijarah financing jointly or partially on profitability at Islamic Commercial Banks in Indonesia for the 2015-2019 Period. The data used are the financial statements of Bank BCA Syariah and Bank Mandiri Syariah which provide quarterly financial reports. The research method used in this research is quantitative descriptive method. This study used the Multiple Linear Regression model, using four classical assumption tests, namely normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. The results of this study indicate that partially mudharabah has no effect on profitability. Musyarakah partially has a positive and significant effect on profitability. Partially ijarah has a positive and significant effect on profitability. Simultaneously mudharabah, musyarakah and ijarah have a significant effect on profitability.